2021
DOI: 10.7861/fhj.2020-0180
|View full text |Cite
|
Sign up to set email alerts
|

Rebooting medical education with virtual grand rounds during the COVID-19 pandemic

Abstract: Social distancing during the coronavirus disease 2019 (COVID-19) pandemic has necessitated drastic changes in the practice of hospital medicine, including the cancellation of many educational activities. At the same time, the emergence of a new disease with a rapidly evolving knowledge base has mandated timely educational updates. To resolve this conflict in our hospital, we substituted 'traditional' grand rounds with 'virtual' grand rounds delivered over Zoom, consisting of a local situation report and operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…Although web-based live communications and team meetings have been mainstays in large corporations and technology companies, [9][10][11][12] the adoption of similar methods of communication and knowledge exchange has been slow in medicine but has been accelerated dramatically in the midst of the COVID-19 pandemic. 5,[13][14][15] Similar to what has been described in initiatives across other medical specialties, [16][17][18] we found that respondents across all groups appreciated the convenience of attending and the convenience of obtaining CMEs at virtual grand rounds. Virtual grand rounds have allowed faculty and residents who normally have clinic or cases scheduled off-site or soon after grand rounds conclude to easily join in either together at an off-site location or individually from their personal electronic devices.…”
Section: Discussionsupporting
confidence: 76%
“…Although web-based live communications and team meetings have been mainstays in large corporations and technology companies, [9][10][11][12] the adoption of similar methods of communication and knowledge exchange has been slow in medicine but has been accelerated dramatically in the midst of the COVID-19 pandemic. 5,[13][14][15] Similar to what has been described in initiatives across other medical specialties, [16][17][18] we found that respondents across all groups appreciated the convenience of attending and the convenience of obtaining CMEs at virtual grand rounds. Virtual grand rounds have allowed faculty and residents who normally have clinic or cases scheduled off-site or soon after grand rounds conclude to easily join in either together at an off-site location or individually from their personal electronic devices.…”
Section: Discussionsupporting
confidence: 76%
“…[11][12][13][14][15][16] A summary of the key recommendations from the literature review is shown in Table 1 and each is discussed in more detail in the further evaluation section. [2][3][4][5][6][9][10][11][12]17 Further evaluation: The 10 recommendations for medical education in a pandemic Recommendation 1: Students must feel safe in order to learn…”
Section: Resultsmentioning
confidence: 99%
“…Key themes were extracted from the abstracts on this basis, and nine papers were selected on this basis for full paper review. [2][3][4][5][6][7][8][9][10] Papers describing the impact of the pandemic on medical education but not offering practical suggestions on how to address this were excluded.…”
Section: A Practical Solution To Medical Education In a Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-center studies of faculty perspectives in other specialties have shown positive correlations with improved attendance. 2,3 This multicenter observational study sought to explore the OB-GYN experience with VGR and to assess perceptions by role (educator vs trainee).…”
mentioning
confidence: 99%